Hubungan Pengetahuan Ibu Tentang Alat Permainan Edukatif (APE) dengan Perkembangan Motorik pada Anak Usia Prasekolah - Rapingah, Siti; Widiyanti, Syifa (Journal of Religion and Public Health, 2021)
Pre-school childrens’ at the age of 3-6 years is called the golden age periode of brain development of children.At this age, children need to be stimulated in order to optimize the development process, one of which is educational games.Many factors affect motoric development in children, one of which is mother's knowledge. This study aims to identify the relationship between mother's knowledge about Educational Game Tools (APE) with motoric development in preschool-aged children. This research is a type of correlational quantitative research. The total population is 380 people. Samples were taken by using multistage area random sampling technique as many as 80 respondents. The analysis used univariate and bivariate using Spearman rank test with = 5%. The results showed that the knowledge of mothers in the good category was 39 (48.8%) and for motoric development which was in the normal category was 41 (51.2%) it can be concluded that there is a relationship between mother knowledge about APE and motoric development in preschoolers. with p value = 0.000 (< 0.05) and r = 0.408. Suggestions for children who are suspect or untestable, it is hoped that the mother/caregiver will stimulate the child's fine motoric development and monitor it according to their age by using KPSP.Keywords: educational game tools, motoric development, pre-school.AbstrakAnak usia 3-6 tahun atau masa pra sekolah disebut sebagai masa keemasan dari pertumbuhan otak anak. Pada usia ini anak harus diberikan rangsangan atau stimulasi agar perkembangan menjadi optimal salah satunya dengan permainan edukatif. Banyak faktor yang mempengaruhi perkembangan motorik pada anak, salah satunya pengetahuan ibu. Penelitian ini bertujuanuntuk mengidentifikasi hubungan pengetahuan ibu tentang Alat Permainan Edukatif (APE) dengan perkembangan motorik pada anak usia prasekolah. Penelitian ini merupakan jenis penelitian kuantitatif korelasional.Jumlah populasi adalah sebanyak 380 orang. Sampel diambil dengan teknik multistage area random sampling sebanyak 80 responden. Analisis yang digunakan univariat dan bivariat menggunakan uji rank spearman dengan α=5%. Hasil penelitianbahwa didapatkan pengetahuan ibu dalam kategori baik sebanyak 39 (48,8%) dan untuk perkembangan motorik yang berada dalam kategori normal adalah sebanyak 41 (51,2%) dapat disimpulkanada hubungan pengetahuan ibu tentang APE dengan perkembangan motorik pada anak usia prasekolah dengan p value = 0,000 (< 0,05) dan r = 0,408. Saranpada anak dengan suspect atau untestable diharapkan ibu/pengasuh menstimulasi perkembangan motorik halus anak serta memonitor sesuai dengan usianya menggunakan KPSPKata Kunci: Alat Permainan Edukatif, Perkembangan Motorik, Pra sekolah